Free radical scavenging, α-glucosidase inhibitory and lipase inhibitory activities of eighteen Sudanese medicinal plants - Sara Mustafa Idris Elbashir; Hari Prasad Devkota; Mikiyo Wada; Naoki Kishimoto; Masataka Moriuchi; Tsuyoshi Shuto; Shogo Misumi; Hirofumi Kai; Takashi Watanabe (BMC, 2018)
Abstract Background Lifestyle-related diseases such as diabetes are steadily increasing worldwide. In Sudan, there are a variety of plant species used traditionally for the treatment of diabetes, obesity and other symptoms which need to be validated through scientific studies for their claimed traditional uses. Therefore, in the current study, the free radical scavenging activity, α-glucosidase inhibitory and pancreatic lipase inhibitory activities of 70% ethanol and water extracts of eighteen Sudanese medicinal plants were investigated using various in vitro assays. Moreover, the cytotoxicity and genotoxicity were assessed for the bioactive plant extracts. Methods Eighteen plants were selected on the basis of their traditional uses and extracted with 70% ethanol and water to obtain thirty-six extracts. The obtained extracts were screened using different in vitro bioassays namely, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, α-glucosidase inhibitory and pancreatic lipase inhibitory assays. Furthermore, the active plant extracts were investigated for their cytotoxicity and genotoxicity on HeLa cell line using HCS DNA Damage Assay. Results Both 70% ethanol and water extracts of Acacia nilotica, Ziziphus spina-christi, Abrus precatorius, and Geigeria alata along with the 70% ethanol extract of Martynia annua showed potent free radical scavenging activity. Regarding the α-glucosidase inhibition assay, both extracts of Acacia nilotica, Ziziphus spina-christi, Geigeria alata, and Cyperus rotundus showed potent activity. In general, 70% ethanol extracts were more potent compared to water extracts with exception of Cordia sinensis and Cymbopogon proximus, for which water extracts also showed potent enzyme inhibitory activity. Similarly, water extracts of Acacia nilotica and Ziziphus spina-christi showed potent inhibitory activity against pancreatic lipase enzyme. Some of the extracts also showed significant genotoxicity and cytotoxicity at the concentration range used for bioactivities. Conclusion The extracts of Acacia nilotica, Ziziphus spina-christi, Geigeria alata, Martynia annua and Abrus precatorius exhibited an appreciable range of activity on antioxidant and enzyme inhibitory assays.